Research on Influencing Factors and Carbon Emission of Power Systems Based on Logarithmic Mean Divisia Index and Big Data Techniques - Weichen Ni (The International Journal of Multiphysics, 2024)
With global warming and the development of urbanization and industrialization, controlling carbon emissions has become an important issue facing all mankind. China’s power sector exceeds 40% of overall societal carbon emissions, so transforming into a green and low-carbon system is what the power system needs. Two key research priorities are further exploring accounting methods for the sector and establishing a robust carbon emission measurement system in China. This paper aims to outline critical factors that influence the emissions of carbon dioxide in the power department in accounting methods based on electricity big data technologies. Then, the assessment of the carbon emissions system built on the Logarithmic Mean Divisia Index (LMDI) and big data technologies is proposed. These technologies enhance the power system’s ability to efficiently monitor and manage its carbon emissions. These technologies help to take hold of its carbon emissions. thus achieving the power system’s ’two-carbon’ objective.